The relationship between employees’ empowerment and job satisfaction in the Sarawak Energy Sdn. Bhd., Kuching/ Amanda Mikeng - Mikeng, Amanda (2016)
Based on its title, this research paper is focused on “The Relationship between Employees’ Empowerment and Job Satisfaction”. The main purposes of this study are to determine which dimension of the psychological empowerment that has the highest relationship towards job satisfaction in Sarawak Energy Sdn. Bhd., Kuching. Descriptive statistic and correlation approach were carried out by using psychological empowerment and job satisfaction questionnaire. Reliability and validity of psychological empowerment and job satisfaction were established. The respondents of this study were employees of Sarawak Energy Sdn. Bhd., Kuching which 70 of them chosen to answered the questionnaire. The finding indicated that competence dimension of psychological empowerment shows highest descriptive statistic for employee empowerment on job satisfaction and meaning dimension of psychological empowerment shown the highest Pearson correlation between employees’ empowerment and job satisfaction in Sarawak Energy Sdn. Bhd. In conclusion, employees’ empowerment has significant relationship with job satisfaction. Thus, this study should be extended for other government and private organizations in Kuching, Sarawak.